LEGAL POLITICS DESA ADAT DALAM MENGATUR KRAMA TAMIU (Studi Kasus di Desa Bayad, Kecamatan Tegalalang, Kabupaten Gianyar) - I Putu Sastra Wibawa (Sekolah Tinggi Agama Hindu Dharma Nusantara Jakarta, 2013)
Abstract Pakraman Village courage and competent in organizing migrants / Krama Tamiu will surely come from the authority of the traditional village autonomy, also sourced from politics and made laws outlined by the provincial government of Bali itself. Krama Tamiu legal political arrangement certainly has a strategic rationale, one which is not just local government is involved in regulating Krama Tamiu , but also involve the participation of traditional village in implementation.However, often times the legal implementation encountered some obstacles and problems, both technical and non-technical issues, such as the one that occurred in the village of Bayad . Thus the researchers wanted to examine and study more about the